1998
DOI: 10.1111/j.1398-9995.1998.tb03952.x
|View full text |Cite
|
Sign up to set email alerts
|

Double‐blind, placebo‐controlled evaluation of sublingual immunotherapy with standardized olive pollen extract in pediatric patients with allergic rhinoconjunctivitis and mild asthma due to olive pollen sensitization

Abstract: For evaluation of the efficacy and the safety of specific sublingual immunotherapy with high allergen dose, 66 children with seasonal asthma, rhinitis, and conjunctivitis due to sensitization to olive pollen were enrolled in a double-blind, randomized, placebo-controlled study between October 1994 and October 1996 in Greece. Thirty-four patients were randomly allocated to the active group, and 32 received placebo. Immunotherapy consisted of olive-allergen extracts (Stallergènes SA) administered sublingually pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
132
2
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 171 publications
(146 citation statements)
references
References 22 publications
6
132
2
6
Order By: Relevance
“…The magnitudes of effect could not be determined in 7 studies. 25,[27][28][29]32,35,36 The risk of bias across these studies was mixed. The strength of evidence is moderate that SLIT decreases medication use.…”
Section: Medication Scoresmentioning
confidence: 99%
See 4 more Smart Citations
“…The magnitudes of effect could not be determined in 7 studies. 25,[27][28][29]32,35,36 The risk of bias across these studies was mixed. The strength of evidence is moderate that SLIT decreases medication use.…”
Section: Medication Scoresmentioning
confidence: 99%
“…25,28 Five studies demonstrated significant improvement in rhinitis/ rhinoconjunctivitis scores with SLIT, compared with placebo, with moderate to strong magnitudes of effect. 33,34,[36][37][38] Four studies did not show significant improvement with SLIT, 25,26,29,32 and 1 of these favored placebo. 26 The strength of evidence is moderate that SLIT improves rhinitis symptoms.…”
Section: Rhinitismentioning
confidence: 99%
See 3 more Smart Citations